Development of Grade 11 Indonesian History Question Exercises on Japanese Occupation in Indonesia (1942-1945) using the Zep Quiz Media - Ardi Tri Yuwono; Andi Sebastian; Gijsbert ter Braake (Yayasan Mutiara Hati Moeslem, 2026)
History learning at the high school level still faces challenges in the form of a lack of media variety and low motivation for students to learn complex material, such as the Japanese Occupation of Indonesia (1942-1945). This research aims to develop a history question exercise based on Zep Quiz that is valid, practical, and potentially effective in practicing historical thinking skills of grade 11 students. The method used is Research and Development (R&D) with a 4-D (Define, Design, Develop, and Disseminate) model. The product was developed in the form of 20-tiered multiple-choice questions from cognitive levels C1 to C5 which were integrated with Zep Quiz gamification features such as avatars, leaderboards, and explanatory feedback, and were equipped with a Student Worksheet as a reflection tool. The validation results of material experts reached 95% and media experts 95.6% with the category of very feasible. The test on 36 students in grade 11-K of Madrasah Aliyah Negeri 1 Kediri City showed that all students managed to access the quiz with an average score of 78.2. The student response questionnaire showed that 94.4% felt motivated and 97.2% were interested in using similar media in the future. The theoretical implication of this research is a synergy model between gamification and historical pedagogy, while the practical implication is the availability of a ready-to-use integrated Zep Quiz Media learning package for teachers.